How the Merdeka Curriculum Enhances the Pancasila Student Profile in Education - Dwi Rahmad Julianto; Ali Mustadi; Anwar Senen; Ujang Sugara (Indonesian Journal of Educational Research and Review)
The implementation of the Merdeka Curriculum places the Pancasila Student Profile Strengthening Project (P5) as a vital element in the learning process. However, its integration with thematic learning, particularly in Natural and Social Sciences (IPAS) subjects, still encounters various conceptual and practical obstacles. This study aims to analyze the alignment between the Learning Outcomes (Capaian Pembelajaran/CP) of IPAS subjects and the dimensions of the Pancasila Student Profile at the elementary school level. This research employed a qualitative approach through a document study method. The population consisted of all IPAS Learning Outcomes for phases A, B, and C at the elementary school level, while the sample included IPAS knowledge Learning Outcomes linked to the six dimensions of the Pancasila Student Profile. Data were analyzed using content analysis techniques on both the IPAS Learning Outcomes document and the Pancasila Student Profile strengthening project guidelines. The results indicated that each dimension of the Pancasila Student Profile can be conceptually integrated with several IPAS Learning Outcomes across all phases. It can be concluded that, theoretically, the Pancasila Student Profile Strengthening Project holds significant potential to be integrated into IPAS learning, serving as a reference for the development of teaching tools based on the Merdeka Curriculum. Its practical implication suggests that these findings can be utilized as a foundation for designing IPAS learning activities aligned with the values of the Pancasila Student Profile.